Tenebrio molitor Larvae-Based Magnetic Polyurea Employed as Crude Oil Spill Removal Tool - Aboelkheir, Mostafa (2022)
Renewable resources constitute an extremely rich and varied set of molecules and polymers produced by natural biological activities. Within the applications of these polymers, a very important application is the use of these materials as a sorber for oils or oil spills. The advantage of these nanocomposites is the fact that they integrate different component materials and their properties into a single component material. They have several applications, ranging from environmental remediation to the development of advanced medical applications. This work proposed using magnetic polyurea composites based on an animal substrate from Tenebrio molitor larvae to perform oil spill clean-up operations under a magnetic field in the presence of 1% and 3% of magnetite to be tested as magnetic crude oil sorber. The obtained materials were characterized by Fourier transform infrared (FTIR) spectroscopy, X-ray Diffraction (XRD), Thermogravimetric Analysis (TGA), Scanning Differential Calorimetry (DSC), and Low-Field Nuclear Magnetic Resonance (LF-NMR 1H). The sorber material is simple to prepare and inexpensive. The use of magnetite as a magnetic charge allowed for the efficient removal of oil from water with about 28 g of oil per gram of sorber. These results are very promising and encouraging for future environmental recovery studies involving magnetite and sustainable polymers.